Synthesis, SAR and Molecular Docking Studies of Certain New Derivatives of 1,2,4-Triazolo [3,4-b][1,3,4] Thiadiazole as Potent Antimicrobial Agents - Sahu, Jagdish K.; Ganguly, Swastika; Yasir, Mohammad (Anti-Infective Agents, 2018)
Background: Today infectious microbial diseases are causing complications world-wide, since resistance to a number of antimicrobial agents (β-lactam antibiotics, macrolides, quinolones, and vancomycin). A range of clinically important species of microorganisms has become a significant health problem globally. Methods: In quest of new antimicrobial agents with enhanced potency, a series of 6-aryl-3-[(2,3,4- substituted) phenyl]-[1,2,4]triazolo [3,4-b][1,3,4] thiadiazole (5a-5l) were synthesized by condensing 4- amino-5-[(2,3,4-substituted) phenyl]-4H-[1,2,4]- triazole-3-thiol (4) with various aromatic carboxylic acids in the presence of phosphorous oxychloride through one-pot reaction. The structures of these newly synthesized compounds were elucidated by elemental analysis, IR, 1H NMR and mass spectral data. All the synthesized compounds were screened for their in vitro antibacterial and antifungal activities against pathogenic microorganisms using two fold serial dilution method. Results: Several compounds showed favorable antimicrobial activity among which, compound 5e exhibited highest activity while compounds 5h and 5d presented promising antimicrobial activity against all the tested microorganisms comparable to reference drugs gentamicin and miconazole. However, when compared to fluconazole, the test compound 5e had lesser estimated binding free energy and predicted inhibitory constant values. Conclusion: From the current study it may be concluded that synthesized compounds are fulfilling in terms of their structural distinctiveness and marked biological properties. The molecular docking studies have amplified the scope of evolving a new class of antimicrobial agents.
Keywords: Triazolothiadiazoles